TEKNIK PEMASARAN SABUN CAIR CUCI PIRING CHEMLIGHT BERBASIS ONLINE DI DESA FAJAR BARU LAMPUNG SELATAN - Ni Lu Gede Juliasih; Pigo Nauli; Nurhasanah Nurhasanah; Agung Abadi Kiswandono (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The strategic location of Desa Fajar Baru gives an opportunity for expanding the entrepreurship in profitable business of liquid soap called chemlight. The mother’s society named PKK Desa Fajar baru accompanied by the Unila Community Team through Unila's DIPA BLU 2016 and 2018 has succeeded in production of Chemlight brand, although it has still produce a simple and based on orders liquid soap. Poorly management in production and sales has an impact of reduction in the profit. Through the community service activities, couching has been made in making production house and online-based marketing (websites and android applications) without leaving conventional systems. The results showed that there was an increase in the knowledge of participants in terms of online marketing of chemlight soap by up to 40%, therefore, this online-based marketing became a trigger for increasing people's welfare.